2008
DOI: 10.1111/j.1461-9563.2008.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Grain aphid population structure: no effect of fungal infections in a 2‐year field study in Denmark

Abstract: 1 Sitobion avenae (F.) is a serious pest in Danish cereal crops. To understand the population genetic structure, aphids were sampled in seven different winter wheat ( Triticum sativum Lamarck) fields throughout Denmark. The aphids were genotyped with seven microsatellite markers. In total, 2075 aphids were collected and 1203 of these were genotyped. 2 The Danish S. avenae populations displayed very high genotypic diversity, high percentages of unique genotypes and low linkage disequilibria; this is likely to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…To ensure enrichment of the library with cDNAs specific to the host-pathogen interaction, we sampled aphids during a natural fungal epidemic. Aphid populations in arable land are typically infected with more than one entomophthoralean species (Jensen et al, 2008). On collection days, E. planchoniana was the most prevalent (15-27% of infected aphids), followed by P. neoaphidis (4-8%), and with only a few percent infected by C. obscurus (Fig.…”
Section: Production Of a Rich Host-pathogen Interaction Cdna Librarymentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure enrichment of the library with cDNAs specific to the host-pathogen interaction, we sampled aphids during a natural fungal epidemic. Aphid populations in arable land are typically infected with more than one entomophthoralean species (Jensen et al, 2008). On collection days, E. planchoniana was the most prevalent (15-27% of infected aphids), followed by P. neoaphidis (4-8%), and with only a few percent infected by C. obscurus (Fig.…”
Section: Production Of a Rich Host-pathogen Interaction Cdna Librarymentioning
confidence: 99%
“…1A and B) was followed during one growth season in a Danish organically grown winter wheat field to determine the appropriate time for sampling potentially infected individuals. Species composition was determined by weekly sampling and incubation of 100 live aphids until spore discharge allowed morphological examination, as described in Jensen et al (2008). When fungal infection prevalence increased, thousands of live aphids were brought into the laboratory (Fig.…”
Section: Biomass Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies that used molecular markers to examine genetic differentiation of S. avenae populations in China and Europe (Simon et al 1999, Fievet et al 2007, Jensen et al 2008, Xu et al 2011, but variations in the limited loci used may not reßect the extent of changes in their life-history traits. We hypothesize that the separation of Qinling Mountains can cause increasing life-history divergence and local adaptation of S. avenae populations in northern and southern Shaanxi Province, thus creating different population structuring patterns in those areas.…”
mentioning
confidence: 98%
“…Integrated pest management (IPM) can be seen as a sustainable control strategy to manage pest insects like aphids [6]. Field observations have shown that aphid populations are commonly regulated by a range of natural enemies, such as predators, parasitoids, and also fungal pathogens [7]. In temperate regions, fungal species from the phylum Entomophthoromycota are important pathogens of aphids [810].…”
Section: Introductionmentioning
confidence: 99%